Saline–alkaline stress in growing maize seedlings is alleviated by Trichoderma asperellum through regulation of the soil environment - Jian Fu (Nature Portfolio, 2021)
Abstract A significant proportion of the land area of Heilongjiang Province, China, is composed of saline–alkaline soil, which severely inhibits maize growth. Although Trichoderma treatment is widely regarded as a promising strategy for improving the soil environment and promoting plant growth, the mechanism through which Trichoderma asperellum enhances maize resistance to saline–alkaline stress is not clear. In this study, we explored the effect of T. asperellum application at different concentrations to soil saline–alkaline environment on the seedlings of two maize cultivars, assessing the biochemical parameters related to oxidation resistance. Increasing spore densities of T. asperellum suspension effectively regulated the soil ion balance in the rhizosphere of maize seedlings, reduced the soil pH by 2.15–5.76% and sodium adsorption ratios by 22.70–54.13%, increased soil nutrient content and enzyme activity, and improved the soil environment for seedling growth. Additionally, T. asperellum treatment increased the maize seedling content of osmo-regulating substances and rate of glutathione:oxidised glutathione (43.86–88.25%) and ascorbate:oxidised ascorbate (25.26–222.32%) by affecting the antioxidant enzyme activity in the roots, increasing reactive oxygen species scavenging, and maintaining the osmotic balance and metabolic homeostasis under saline–alkaline stress. T. asperellum also improved the saline–alkaline tolerance of maize seedlings by improving the root growth characteristics. Moreover, results showed that Trichoderma applied at high concentration had the greatest effect. In conclusion, improvement in the saline–alkaline tolerance of maize seedlings by T. asperellum under saline–alkaline soil conditions may be achieved through diverse effects that vary among maize cultivars.